Medial Plantar Artery Flap for Soft Tissue Coverage of Heel Defect: A Case Report - Ramadhani Hengki Wijaya; Achmad Fachrizal (Journal Orthopaedi and Traumatology Surabaya)
Background: Numerous flap options exist for providing soft tissue coverage for defects on the heel region. This study presents a case where a bone-exposed wound on the left heel region was successfully reconstructed using a medial plantar artery flap.